CsPOM1, a DYRK Family Kinase, Plays Diverse Roles in Fungal Development, Virulence, and Stress Tolerance in the Anthracnose Pathogen Colletotrichum scovillei - Shin, Jong-Hwan; Kim, Hee-Yeong; Fu, Teng; Lee, Kwang-Ho; Kim, Kyoung Su (Frontiers in Cellular and Infection Microbiology, 2022)
Colletotrichum scovillei is the major anthracnose fungus of sweet pepper and chili pepper (Capsicum annuum L.), causing significant losses in the yield and quality of the pepper fruits. Molecular mechanisms governing development and pathogenicity have been widely studied in many foliar fungal pathogens, but the information on fruit diseases is still limited. In this study, we determined the functional roles of the dual-specificity tyrosine phosphorylation-regulated kinase CsPOM1 in C. scovillei. Knockout mutant for CsPOM1 gene was obtained via homology-dependent gene replacement. The ΔCspom1 mutant exhibited a reduction in vegetative growth on osmotic stress, surface hydrophobicity, and conidiation compared with wild-type. Conidia of the ΔCspom1 mutant were already two-celled before inoculation on an induction surface, indicating that CsPOM1 negatively regulates conidial cell division. The ΔCspom1 mutant, similar to wild-type, formed appressoria on the plant surface, but was significantly reduced on hydrophobic coverslips, probably due to a defect in the recognition of surface hydrophobicity. Treatment of conidia with cutin monomers restored appressorium formation on hydrophobic coverslips in the ΔCspom1 mutant. On pepper fruits, the ΔCspom1 mutant exhibited delayed penetration and invasive growth, leading to significantly reduced virulence. Collectively, the results showed that CsPOM1 is important for stress tolerance, conidiation, surface hydrophobicity, appressorium formation, and virulence in C. scovillei.